Cyclo(RGD)‐Decorated Reduction‐Responsive Nanogels Mediate Targeted Chemotherapy of Integrin Overexpressing Human Glioblastoma In Vivo. Issue 6 (16th November 2016) - Chen, Wei; Zou, Yan; Zhong, Zhiyuan; Haag, Rainer
Abstract : Cyclo(Arg‐Gly‐Asp) peptide (cRGD) decorated disulfide (SS) containing poly(vinyl alcohol) nanogels (cRGD‐SS‐NGs) with an average diameter of 142 nm prepared by inverse nanoprecipitation, "click" reaction, and cRGD conjugation are developed for targeted treatment of integrin overexpressing human glioblastoma in vivo. Doxorubicin (DOX) release from cRGD‐SS‐NGs is highly inhibited under physiological conditions, while accelerated at endosomal pH and in response to cytoplasmic concentration of glutathione. Confocal microscopy shows that cRGD‐SS‐NGs facilitate the cellular uptake and intracellular DOX release in αv β3 integrin overexpressing human glioblastoma U87‐MG cells. DOX‐loaded cRGD‐SS‐NGs present much better killing activity toward U87‐MG cells than that for nontargeted nanogels determined by MTT assay. The in vivo imaging and biodistribution studies reveal that DOX‐loaded cRGD‐SS‐NGs have a much better tumor targetability toward human U87‐MG glioblastoma xenograft in nude mice. Also the tumor growth is effectively inhibited by treatment with DOX‐loaded cRGD‐SS‐NGs, while continuous tumor growth is observed for mice treated with nondecorated nanogels as well as free DOX. Furthermore, the treatment with DOX‐loaded cRGD‐SS‐NGs has much fewer side effects, rendering these nanogels as a new platform for cancer chemotherapy in vivo. Abstract : Active targeting of cyclo(Arg‐Gly‐Asp) peptide (cRGD) decorated disulfide (SS) containing polyvinyl alcohol nanogels (cRGD‐SS‐NGs) for efficient treatment of human glioblastoma. These cRGD‐SS‐NGs give (i) super stability for circulation and tumor accumulation, (ii) enhanced cellular uptake via receptor‐mediated endocytosis, and (iii) pH and reduction triggered intracellular drug release, resulting in potent antitumor effect.